SU5416 attenuated lipopolysaccharide-induced acute lung injury in mice by modulating properties of vascular endothelial cells - Huang X; Zhu J; Jiang Y; Xu C; Lv Q; Yu D; Shi K; Ruan Z; Wang Y (Dove Medical Press, 2019)
Xuqing Huang,1,* Junqi Zhu,2,* Yuyue Jiang,1 Changqing Xu,1 Qun Lv,1 Dongwei Yu,1 Kai Shi,1 Zhaoyang Ruan,1 Yan Wang11Department of Respiratory Medicine, Affiliated Hospital of Hangzhou Normal University, Hangzhou, Zhejiang, People’s Republic of China; 2Department of Clinical Medicine, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People’s Republic of China*These authors contributed equally to this workBackground and aim: A potent and selective vascular endothelial growth factor receptor (VEGFR) inhibitor SU5416, has been developed for the treatment of solid human tumors. The binding of VEGF to VEGFR plays a crucial role in the pathophysiology of respiratory disorders. However, the impact of SU5416 on lipopolysaccharide (LPS)-induced acute lung injury (ALI) remains unclear. Thus, this study aimed to illuminate the biofunction of SU5416 in the mouse model of ALI.Methods: Wild-type (WT) and toll-like receptor 4 (TLR4)-deﬁcient (TLR4−/-) C57BL/6 mice were used to establish LPS-induced ALI model. The primary pulmonary microvascular endothelial cell (PMVEC) was extracted for detection of endothelial barrier function.Results: LPS significantly increased the number of inflammatory cells and inflammatory cytokines in bronchoalveolar lavage fluid (BALF). In addition, LPS increased alveolar epithelial cells injury, inflammation infiltration and vascular permeability of PMVEC in WT and TLR4−/- mice. Western blotting experiment indicated VEGF/VEGFR and TLR4/NF-κB pathways were involved in the progression of LPS-stimulated ALI. Consistent with previous research, dexamethasone treatment appeared to be an effective therapeutic for mice with ALI. Moreover, treatment with SU5416 dramatically attenuated LPS-induced immune responses in mice lung tissues via inhibiting VEGF/VEGFR and TLR4/NF-κB pathways. Finally, SU5416 also decreased vascular permeability of PMVEC in vitro.Conclusion: SU5416 ameliorated alveolar epithelial cells injury and histopathological changes in mice lung via inhibiting VEGF/VEGFR and TLR4/NF-κB signaling pathways. We also confirmed that SU5416 could restrain vascular permeability in PMVEC through improving the integrity of endothelial cell. These findings suggested that SU5416 may serve as a potential agent for the treatment of patients with ALI.Keywords: SU5416, lipopolysaccharide, acute lung injury, inflammatory cytokines